PENGARUH KECEMASAN BERKOMPUTER DAN KEPRIBADIAN TERHADAP KINERJA AKUNTAN PENDIDIK STUDI KASUS PADA PERGURUAN TINGGI DI SURABAYA - Dedy Kushariyadi; Endrik Vita Yuliana (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
This Study is aimed to examine the effect of computer anxiety and big five personality on the performance of accounting educators. This model is tested on 73accounting educators at universities in Surabaya. Primary data were obtained directly, through the distribution of questionnaires. Testing is done in two steps, first is multiple linear regression analysis and the second is hypothesis testing. The results of the analysis of the data from this study show that: (1) Computer anxiety had not effect on the performance of accounting educators. (2) Big five personality is influential on the performance of accounting educators